'Race', communication and the caring professions - Robinson, Lena. (Open University Press, 1998)
Influences of racial identity states on interethnic communication. Beliefs, attitudes, values and interethnic communication. Culture and interethnic communication. The role of language in interethnic communication. Nonverbal communication in interethnic settings. Interpersonal perception and interethnic communication.